Incorporating priorities for waiting customers in the hypercube queuing model with application to an emergency medical service system in Brazil - Souza, Regiane Máximo de [UNESP]; Morabito, Reinaldo; Chiyoshi, Fernando Y.; Iannoni, Ana Paula (Elsevier B.V., 2015)
Emergency medical services (EMS) assist different classes of patients according to their medical seriousness. In this study, we extended the well-known hypercube model, based on the theory of spatially distributed queues, to analyze systems with multiple priority classes and a queue for waiting customers. Then, we analyzed the computational results obtained when applying this approach to a case study from an urban EMS in the city of Ribeirao Preto, Brazil. We also investigated some scenarios for this system studying different periods of the day and the impact of increasing the demands of the patient classes. The results showed that relevant performance measures can be obtained to analyze such a system by using the analytical model extended to deal with queuing priority. In particular, it can accurately evaluate the average response time for each class of emergency calls individually, paying particular attention to high priority calls. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: OR in health services; Hypercube model; Queuing priority; Emergency medical services; SAMU